Intact cord resuscitation in newborns with congenital diaphragmatic hernia: insights from a lamb model - Baptiste Teillet; Baptiste Teillet; Florian Manœuvrier; Florian Manœuvrier; Céline Rougraff; Céline Rougraff; Capucine Besengez; Laure Bernard; Laure Bernard; Anne Wojtanowski; Louise Ghesquieres; Louise Ghesquieres; et al. (Frontiers Media S.A., 2023)
IntroductionCongenital diaphragmatic hernia (CDH) is a rare condition characterized by pulmonary hypoplasia, vascular dystrophy, and pulmonary hypertension at birth. Validation of the lamb model as an accurate representation of human CDH is essential to translating research findings into clinical practice and understanding disease mechanisms. This article emphasizes the importance of validating the lamb model to study CDH pathogenesis and develop innovative therapeutics.Material and methodsAt 78 days of gestation, the fetal lamb's left forelimb was exposed through a midline laparotomy and hysterotomy, and a supra diaphragmatic thoracotomy was performed to allow the digestive organs to ascend into the thoracic cavity. At 138 ± 3 days of gestation, lambs were delivered via a cesarean section; then, with umbilical cord intact during 1 hour, the lambs were mechanically ventilated with gentle ventilation in a pressure-controlled mode for 2 h.ResultsCDH lambs exhibited a lower left lung-to-body weight ratio of 5.3 (2.03), p < 0.05, and right lung-to-body weight ratio of 8.2 (3.1), p < 0.05. They reached lower Vt/kg (tidal volume per kg) during the course of the resuscitation period with 1.2 (0.7) ml/kg at 10 min and 3 (1.65) ml/kg at 60 min (p < 0.05). Compliance of the respiratory system was lower in CDH lambs with 0.5 (0.3) ml/cmH2O at 60 min (p < 0.05) and 0.9 (0.26) ml/cmH2O at 120 min (p < 0.05). Differences between pre- and postductal SpO2 were higher with 15.1% (21.4%) at 20 min and 6.7% (14.5%) at 80 min (p < 0.05). CDH lambs had lower differences between inspired and expired oxygen fractions with 4.55% (6.84%) at 20 min and 6.72% (8.57%) at 60 min (p < 0.05). CDH lamb had lower left ventricle [2.73 (0.5) g/kg, p < 0.05] and lower right ventricle [0.69 (0.8), p < 0.05] to left ventricle ratio.DiscussionCDH lambs had significantly lower tidal volume than control lambs due to lower compliance of the respiratory system and higher airway resistance. These respiratory changes are characteristic of CDH infants and are associated with higher mortality rates. CDH lambs also exhibited pulmonary hypertension, pulmonary hypoplasia, and left ventricle hypoplasia, consistent with observations in human newborns. To conclude, our lamb model successfully provides a reliable representation of CDH and can be used to study its pathophysiology and potential interventions.